2014
DOI: 10.1116/1.4881995
|View full text |Cite
|
Sign up to set email alerts
|

Selective Raman modes and strong photoluminescence of gallium selenide flakes on sp2 carbon

Abstract: Two-dimensional materials awakened a strong interest in the scientific and technological communities due to their exceptional properties that can be tuned by the material thickness and chemistry. In order to correlate optical properties with crystallographic structure and morphology, in this work, the authors aim at studying GaSe nanoflakes deposited on highly ordered pyrolytic graphite by means of atomic force microscopy, Raman, and photoluminescence (PL) spectroscopies. The authors found that the basal plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“… 31 They observed that the edge effect is strongly dependent on the excitation wavelength. It was recently showed that GaSe flakes also display high anisotropy in the optical properties at the crystal edges 18 . In our case, the photon energy of the SHG is below the band-gap of GaSe (~2.1 eV) 32 and the SHG signal decreases significantly near the edges of the flake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 They observed that the edge effect is strongly dependent on the excitation wavelength. It was recently showed that GaSe flakes also display high anisotropy in the optical properties at the crystal edges 18 . In our case, the photon energy of the SHG is below the band-gap of GaSe (~2.1 eV) 32 and the SHG signal decreases significantly near the edges of the flake.…”
Section: Resultsmentioning
confidence: 99%
“…For layered gallium selenide, PL has been observed in the wavelength range around 620 nm–640 nm 17 . High anisotropy in the Raman spectra and PL of GaSe flakes was recently reported showing the rich physics at the mesoscale with respect to the bulk phase 18 . Bulk gallium selenide is also a well-known material for nonlinear optics and has been used for second-harmonic generation (SHG) at near- and mid-infrared (IR) wavelengths 19 20 21 .…”
mentioning
confidence: 92%
“…[24] with deviations of about 1 cm −1 , and the thickness variation of the lowest A 1 mode are in agreement with the experimental findings, we report some discrepancies for the highest A 2 mode. We trace back the small differences between measurements [14,23,24] and our calculations to the presence of a substrate in experimental setups, whereas only freestanding nanosheets are theoretically investigated.…”
Section: Raman and Ir Spectramentioning
confidence: 66%
“…The consequent LO-TO splitting amounts to 30 cm −1 . Raman measurements reveal an intense peak at 305.2 [14] -306 [24] -307.8 cm −1 [23] (A 1 ) and an E mode at 211 cm −1 [24] -213 cm −1 [23]. A peak for E mode around 208 cm −1 appears in experimental Raman spectrum [14] just for the bulk sample, while a peak at 230 cm −1 is measured in single or double tetralayer samples accompained by a shift of about 3 cm −1 to lower frequencies in thicker, few-tetralayer samples.…”
Section: Raman and Ir Spectramentioning
confidence: 99%
See 1 more Smart Citation